Thermoelectric Materials: High Thermoelectric Performance in n‐Type Perylene Bisimide Induced by the Soret Effect (Adv. Mater. 45/2020). Issue 45 (10th November 2020) - Jiang, Qinglin; Sun, Hengda; Zhao, Duokai; Zhang, Fengling; Hu, Dehua; Jiao, Fei; Qin, Leiqiang; Linseis, Vincent; Fabiano, Simone; Crispin, Xavier; Ma, Yuguang; Cao, Yong
Abstract : The discovery of efficient n‐type organic thermoelectric materials is key to state‐of‐the art thermoelectric materials and can enable the design of efficient and fully organic thermoelectric generators. In article number 2002752, Dehua Hu, Xavier Crispin, Yuguang Ma, and co‐workers develop a novel n‐type perylene bisimide mixed‐ion–electron conductor with record‐high thermoelectric properties induced by the Soret effect.